Analisis Kerja Sama Keamanan Filipina Dengan Amerika Serikat dan China Dalam Konflik Kepulauan Spratly (2016-2024) - Satriana, Grachella (Jurnal Sosial-Politika, 2025)
The Spratly Islands dispute has emerged as a major source of tension in Southeast Asian geopolitics due to China's increasingly assertive territorial claims and artificial island-building activities. This study examines how the leadership transition from Rodrigo Duterte (2016-2022) to Ferdinand Marcos Jr. (2022-2024) fundamentally altered Philippine security cooperation with the United States in the context of the Spratly Islands conflict. Using a qualitative research methodology with explanatory analysis, this study integrates Neoclassical Realism theory with the concepts of bandwagoning and balancing to analyze how domestic factors mediate foreign policy responses to consistent external pressures. The findings suggest that despite facing identical structural threats from Chinese expansion in the Spratly Islands, the Philippines has adopted very different strategic approaches under different leaderships. Duterte's bandwagoning strategy, characterized by